PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPA KELAS VIII DI SMP NEGERI 1 RINDI - Irene Ana Awang; Anita Tamu Ina; Audrey Louise Makatita (BEST Journal (Biology Education, Sains and Technology), 2023)
This study aims to describe the application of learning models Example  Non Example assisted by media images in improving science learning outcomes at SMP Negeri 1 Rindi. This type of research is Classroom Action Research (CAR) with a quantitative descriptive approach. Using two cycles, each cycle consists of several stages including: planning, action, observation and reflection. The subjects of this study were students in class VIII A, totaling 30 people. Data collection techniques and instruments used in this study were tests, observations and documentation. The measurement of learning outcomes is focused on the cognitive and psychomotor domains.The results of the research show the application of the learning model Example Non Example aided by media imagescan improve student learning outcomes in science subjects. This increase can be seen during the pre-cycle, cycle I and cycle II through the learning carried out. At the pre-cycle stage, there were 11 students who completed with a percentage of 37% while those who did not complete were 19 students with a percentage of 63%. In cycle I, there were 22 students who completed with a percentage of 73%, while those who did not complete were 8 students with a percentage of 27%. In cycle II, there were 26 students who completed with a percentage of 87% while those who did not complete were 4 students with a percentage of 13%. It can be concluded that the application of learning models Example Non Example aided by media imagescan improve science learning outcomes class VIII Aat Rindi 1 Public Middle School.